Analisa Keamanan Data Teks Dengan Menerapkan Kriptografi RSA Dan Steganografi LSB - Lindia Ali Fitriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
For various reasons, security and confidentiality are needed in data communication. There have been several attempts to deal with the issue of security of confidential data sent over the Internet, including using cryptographic and steganographic techniques. Cryptography is the science and art of maintaining the confidentiality of a message by encoding it in a form that cannot be understood anymore. Cryptographic techniques can arouse suspicion of third parties who are not entitled to receive information because the message is disguised by changing the original message as if it were unreadable. Furthermore, the third party will have the desire to find out the contents of the secret message and try to solve the real information. Whereas steganography further reduces suspicion because a message disguised is hidden in other messages. Steganography can disguise messages into a media without other people realizing that the media has inserted a message. This is because the output of steganography is data that has the same form of perception as the original data when viewed using human senses in cryptography can be seen and realized directly by the human senses. In steganography, confidential data is inserted into other data called cover-objects and produce stego-objects (the results of steganography). To secure messages using steganography techniques LSB steganography is used and uses the RSA method. Keywords: Cryptography, Steganography, RSA and LSB Methods.